Gas phase cluster studies using a desk-top size soft x-ray laser for single photon ionization - Heinbuch, Scott, author; Rocca, Jorge G., advisor (Colorado State University. Libraries, 2009)
This dissertation reports the study of the structure and reactivity of clusters using a new mass spectrometry approach in which the ionization is produced by high energy photons generated by a desk-top size soft x-ray (SXR) laser. The work was motivated by the importance that catalytic processes have in enhancing the rate of gas phase chemical reactions such as the manufacture of hydrocarbons, polymers, drugs, sulfuric acid, fertilizers, pesticides, etc., many forms of pollution control, development of robust mirror coatings for extreme ultraviolet (EUV) lithography, and hydrogen storage for clean energy applications. Extensive mass spectrometry studies have shown that gas phase nanoclusters are effective model systems to study surface reactions in the bulk phase. However, the use of multi-photon ionization or electron impact ionization sources results in cluster fragmentation, limiting the information gained about the neutral cluster parent. Our approach uses the 26.5 eV photons of a compact capillary discharge driven laser to ionize clusters by single photon events, avoiding the cluster fragmentation associated with multi-photon ionization. The high photon energy also allows the detection of neutral clusters and small molecule reaction products with high ionization energies. Experiments were conducted for several types of clusters including van der Waals clusters, metal oxides, and metal oxide reactions. Density Functional Theory (DFT) calculations were employed to elucidate cluster geometries, properties, and reaction mechanisms. For hydrogen/van der Waals clusters, the unimolecular dissociation rate constants for reactions involving loss of one neutral molecule were calculated and neutral cluster temperature were estimated. The results of metal oxide clusters experiments and calculations suggest that SO2 can be reduced and oxidized by oxygen deficient and oxygen rich vanadium oxide clusters, respectively. Three SO3 formation mechanisms are proposed, and several condensed phase catalytic cycles are suggested based on SO3 formation mechanisms. Other experiments showed that C=C bonds of alkenes can be broken on neutral vanadium oxide oxygen rich clusters with the general structure VO3(V2O 5)n=0,1,2.... DFT calculations provide a mechanistic explanation for the general reaction in which the C=C double bond of alkenes are broken. New results also help to elucidate the selective catalytic reduction of NO using NH3 on a vanadium oxide catalyst. A separate set of experiments to identify capping layer materials for extreme EUV optical coatings that are resistive to carbon contamination. Results show that oxidized Hf and Zr are much less reactive than Ti or Si oxide, and might lead to capping layers that might extend lifetimes of EUV mirror coating upon EUV irradiation. Zr oxide was found to be less reactive than Hf oxide. The set of results demonstrate the potential of compact soft-ray lasers as new tools for chemistry and photo-physics studies with intense soft x-ray light in small laboratory environments.
Keywords: gas phase cluster; molecular beams; single photon ionization; soft x-ray laser; physical chemistry; electrical engineering; optics